Free play and pedagogical play: a multiple-case study of teachers’ views of play in Chinese early learning centers - Wang, Xinxin; Ye, Pingzhi; Qiao, Tianqi (Frontiers in Education, 2024)
Grounded in theories of globalization, this qualitative case study aimed to explore the understanding of play among Chinese teachers in private, for-profit Western style early learning centers. The study encompassed 16 Chinese teachers working in four Western-style early learning centers. Data were gathered through semi-structured interviews. Following separate thematic analyses of each case, a cross-case analysis was conducted to compare and contrast the emerging themes, elucidating both commonalities and distinctions across the four cases. The findings from all four cases revealed a categorization of play into two main types: “play in class'” and “play out of class”. “Play out of class” was characterized as unstructured, enjoyable, and creative, emphasizing child autonomy and spontaneous learning. In contrast, “play in class” pertained to play-based curricula that were thoughtfully designed to align with specific teaching goals and learning objectives. It was seen as a structured method for fostering learning, highlighting the developmental appropriateness of such approaches. These findings underscore the educators’ recognition of the significance of play; however, it also illustrates that their perceptions have been shaped by the prevailing emphasis on children’s achievements in Chinese society.